2016
DOI: 10.1111/iej.12594
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the addition of nanoparticulate calcium carbonate on setting time, dimensional change, compressive strength, solubility and pH of MTA

Abstract: Nanoparticulate calcium carbonate had a cubic morphology with few impurities. The addition of nanoparticulate calcium carbonate to MTA accelerated the setting time, decreased compressive strength and, after 30 days, resulted in lower dimensional change (G2), higher solubility and a higher pH.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(30 citation statements)
references
References 41 publications
(64 reference statements)
3
24
1
Order By: Relevance
“…Compressive strength indicates the quality of hydration process and increased amount of compressive strength over time in both groups in our study is consistent with the results of previous studies (5,15,26). This indicates that MTA was hydrated from day 4 to 21 and obtained its strength to some extent.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Compressive strength indicates the quality of hydration process and increased amount of compressive strength over time in both groups in our study is consistent with the results of previous studies (5,15,26). This indicates that MTA was hydrated from day 4 to 21 and obtained its strength to some extent.…”
Section: Discussionsupporting
confidence: 93%
“…Compressive strength of hydraulic cement is as an indicator of its hydration reaction and in fact is indirectly an indication of the setting process of the material. This physical property is affected by the type of MTA, the liquid with which it is mixed, the condensing pressure and techniques used to mix the powder and liquid (14,15). …”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have concluded that nanomodification of MTA increased the surface area of the powder and the surface reaction resulting in better hydration of particles and more calcium hydroxide formation that increases its chemical reactivity (38,39) . Furthermore, the nanomodification of MTA increased the release of calcium ions in post setting time, which can significantly influence the induction of reparative dentin formation of human dental pulp cells (40) .…”
Section: Discussionmentioning
confidence: 99%
“…The pH of the water in which the samples were immersed in the solubility test was measured at 1 h, 24 h, and 7 days. The measurements were taken using a pH meter (JENWAY,3505 PH Meter, England) precalibrated against standarad solutions of known pH (7.0) and a constant temperature (25°C) [14] .…”
Section: Phmentioning
confidence: 99%
“…Subsequently, a Vicat indenter of 400 ± 5 g with a flat ended needle of 1.0 ± 0.1 mm in diameter was lowered vertically onto the surface of the test material which initially marked the surface with an indentation. This process was repeated until the mark was no longer visible, and the cement setting time was considered from the start of mixing until this moment [14,17,18] .…”
Section: Setting Timementioning
confidence: 99%